Workload, Compensation, and Employee Loyalty: Mediating Role of Job Satisfaction in Islamic Banking - Choiriyah Choiriyah; Abid Djazuli; Tiara Suci Anggraini; Mister Candera; Desi Ulpa A (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study aims to determine the influence of workload and compensation on job loyalty through employee job satisfaction as an intervening variable. The object in this study is an employee of Bank Sumsel Babel Palembang Sharia Branch.Research Methodology: Sampling technique using probability sampling method with cluster random sampling method. The research method used is associative research using the type of primary data obtained from the results of questionnaire answers. The analysis technique used is Structural Equation Modeling (SEM) with SMART-PLS software.Results: The results of this study show: There is a significant influence of workload and compensation on employee work loyalty at Bank Sumatra Babel Sharia, Palembang Branch; There is a significant influence of workload and compensation on employee work satisfaction at Bank Sumatra Babel Sharia, Palembang Branch; There is a significant influence of job satisfaction on employee work loyalty at Bank Sumatra Babel Syariah, Palembang Branch.Conclusions: Workload and compensation significantly influence job loyalty and job satisfaction. Job satisfaction also significantly affects loyalty and mediates the relationships at Bank Sumsel Babel Sharia Branch Palembang.Limitations: The study is limited to one branch, uses self-reported cross-sectional data, and excludes other determinants such as leadership, organizational culture, and career development variables.Contributions: This study enriches Human Resource Management (HRM) literature by confirming job satisfaction’s mediating role and provides managerial insights for improving workload management and compensation systems in Islamic banking institutions.